Cellular radio : principles and design - Macario, R. C. V. (Raymond Charles Vincent) (McGraw-Hill, 1997)
Cellular Radio, 2nd edition, gives engineers, managers, and technicians an up-to-the-minute, easily understood handle on every aspect of this exciting field. This newly revised Second Edition features complete, thoroughly illustrated coverage of cellular radio design principles, cellular radio signaling, digital cellular design - two new added chapters, multipath propagation problems, modulation techniques, speech coding, spectral efficiency considerations, layout optimization, maximization of traffic capability, complete North American and European standards, summary of ALL major worldwide cellular systems, and a wealth of new tables and diagrams.